2001
DOI: 10.1016/s0002-9440(10)63010-6
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Is Down-Regulated in Human Ovarian Carcinoma and Acts as a Candidate Tumor Suppressor Gene

Abstract: To identify novel markers differentially expressed in ovarian cancer versus normal ovary, we hybridized microarrays with cDNAs derived from normal human ovaries and advanced stage ovarian carcinomas. This analysis revealed down-regulation of the caveolin-1 gene (CAV1) in ovarian carcinoma samples. Suppression of CAV1 in ovarian carcinomas was confirmed using a tumor tissue array consisting of 68 cDNA pools from different matched human tumor and normal tissues. Immunohistochemistry demonstrated expression of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
220
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(228 citation statements)
references
References 32 publications
8
220
0
Order By: Relevance
“…We observed decreased expression of caveolin-1 in OVCA cell lines. This observation confirms data published by others (Racine et al, 1999;Bender et al, 2000;Wiechen et al, 2001) that reported loss of caveolin-1 expression in serous ovarian tumors and that forced expression of the gene in a OCa cell line Progesterone-regulated, anti-tumor genes for ovarian cancer V Syed et al (OVCAR-3) resulted in decreases in cell growth and soft agar colony formation (Wiechen et al, 2001). In concordance, we found ectopic expression of caveolin-1 in OVCA cell lines significantly reduced cell growth, soft agar colony formation, and cell motility, but increased caspase-3 activity.…”
Section: Discussionsupporting
confidence: 92%
“…We observed decreased expression of caveolin-1 in OVCA cell lines. This observation confirms data published by others (Racine et al, 1999;Bender et al, 2000;Wiechen et al, 2001) that reported loss of caveolin-1 expression in serous ovarian tumors and that forced expression of the gene in a OCa cell line Progesterone-regulated, anti-tumor genes for ovarian cancer V Syed et al (OVCAR-3) resulted in decreases in cell growth and soft agar colony formation (Wiechen et al, 2001). In concordance, we found ectopic expression of caveolin-1 in OVCA cell lines significantly reduced cell growth, soft agar colony formation, and cell motility, but increased caspase-3 activity.…”
Section: Discussionsupporting
confidence: 92%
“…The serine protease inhibitor maspin suppresses breast cancer progression in vivo and in vitro, 38 -40 yet in estrogen receptor-positive breast cancer, high levels of maspin correlate with shorter survival time. 41 Caveolin-1 acts as a growth suppressor in breast and ovarian cancers, 7,42 but induces proliferation in NSCLCs 10 and in prostate cancer cells. 36 It is remarkable that in lung tumors, the growth-promoting effect of caveolin-1 is restricted to NSCLCs, whereas in small cell lung carcinomas (SCLCs), the protein is down-regulated and has retained its tumor-suppressing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Its re-expression in cell lines derived from these tumors can be achieved via treatment with 5-aza-2Јdeoxycytidine and leads to the inhibition of cell growth and survival. [7][8][9][10] The H-REV107-like genes comprise a novel class II tumor suppressor family. 11,12 Two members of this family, murine H-rev107-1 and human HRASLS, were demonstrated to be suppressed in tumors and tumor cell lines due to promoter methylation, and their re-expression was observed after treatment with 5Ј-aza-deoxycytidine.…”
mentioning
confidence: 99%
“…The presence of CpG-rich regions does not immediately implicate them as regulated by methylation in general or specifically in breast epithelial cells since more than 50% of all human genes may have associated CpG clusters (Murphy and Jirtle, 2001). Only three of these genes have been shown to be hypermethylated in human cancer, CAV1, THBS1, and TNFRSF10B (Li et al, 1999;Cui et al, 2001;Wiechen et al, 2001;Oue et al, 2003;van Noesel et al, 2003). Of these, THBS1 and CAV1 methylation have been linked specifically to breast cancer (Engelman et al, 1999;Li et al, 1999).…”
Section: Discussionmentioning
confidence: 99%